EST-SSR marker development based on RNA-sequencing of E. sibiricus and its application for phylogenetic relationships analysis of seventeen Elymus species - Zhang, Zongyu (BMC Plant Biol, 2019)
BACKGROUND: Elymus L. is the largest genus in the tribe Triticeae Dumort., encompassing approximately 150 polyploid perennial species widely distributed in the temperate regions of the world. It is considered to be an important gene pool for improving cereal crops. However, a shortage of molecular marker limits the efficiency and accuracy of genetic breeding for Elymus species. High-throughput transcriptome sequencing data is essential for gene discovery and molecular marker development. RESULTS: We obtained the transcriptome dataset of E. sibiricus, the type species of the genus Elymus, and identified a total of 8871 putative EST-SSRs from 6685 unigenes. Trinucleotides were the dominant repeat motif (4760, 53.66%), followed by dinucleotides (1993, 22.47%) and mononucleotides (1876, 21.15%). The most dominant trinucleotide repeat motif was CCG/CGG (1119, 23.5%). Sequencing of PCR products showed that the sequenced alleles from different Elymus species were homologous to the original SSR locus from which the primer was designed. Different types of tri-repeats as abundant SSR motifs were observed in repeat regions. Two hundred EST-SSR primer pairs were designed and selected to amplify ten DNA samples of Elymus species. Eighty-seven pairs of primer (43.5%) generated clear and reproducible bands with expected size, and showed good transferability across different Elymus species. Finally, thirty primer pairs successfully amplified ninety-five accessions of seventeen Elymus species, and detected significant amounts of polymorphism. In general, hexaploid Elymus species with genomes StStHHYY had a relatively higher level of genetic diversity (H = 0.219, I = 0.330, %P = 63.7), while tetraploid Elymus species with genomes StStYY had low level of genetic diversity (H = 0.182, I = 0.272, %P = 50.4) in the study. The cluster analysis showed that all ninety-five accessions were clustered into three major clusters. The accessions were grouped mainly according to their genomic components and origins. CONCLUSIONS: This study demonstrated that transcriptome sequencing is a fast and cost-effective approach to molecular marker development. These EST-SSR markers developed in this study are valuable tools for genetic diversity, evolutionary, and molecular breeding in E. sibiricus, and other Elymus species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1825-8) contains supplementary material, which is available to authorized users.